2021
DOI: 10.1002/adem.202100170
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cooling Rates on the Microstructure and Mechanical Properties of Aluminum Titanate Flexible Ceramic

Abstract: Herein, aluminum titanate (Al2TiO5, AT) flexible ceramics with different cooling rates (program‐controlling cooling (10 and 20 °C min−1), air cooling (≈400 °C min−1), and water cooling (>1000 °C min−1) are fabricated by reaction sintering of Al2O3 and TiO2. The effect of cooling rates on microstructures and the mechanical properties of AT ceramics are systematically investigated. The microcrack width and density of AT ceramics with different cooling rates are statistically calculated. In addition, the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This observation suggests that the sintered polycrystal may exhibit low strength. The problem of improving the mechanical parameters of tialite-made polycrystals is now widely discussed in the literature [ 20 , 21 , 27 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that the sintered polycrystal may exhibit low strength. The problem of improving the mechanical parameters of tialite-made polycrystals is now widely discussed in the literature [ 20 , 21 , 27 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Tialite is characterized by the high anisotropy of its thermal expansion coefficients [ 5 ]. As a result of the formation of a complex stress state in the material, micro and macro cracks are formed in the material during its cooling after reaction sintering [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. These cracks provide desirable properties, such as a low macroscopic thermal expansion coefficient [ 22 ], low thermal conductivity [ 23 , 24 , 25 ], and, thus, high resistance to thermal shock [ 1 , 11 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, because the formation of magnesium titanate crystal nuclei reduces the activation energy, 9 it is conducive to the formation of aluminum titanate crystal nuclei, which can reduce the sintering temperature 25,26 . Moreover, aluminum titanate has high thermal expansion anisotropy (α a ≈ 11 × 10 −6 K −1 , α b ≈ 21 × 10 −6 K −1 , α c ≈ −3 × 10 −6 K −1 ), 27 which produces a large number of microcracks during the cooling process, resulting in low mechanical strength 28,29 . Studies have shown that second phase (mullite, feldspar, talc, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AT ceramic has been reported to be very effective in improving the average efficiency of planar perovskite solar cells 9 . Very recently, AT ceramics appear in several reports as the raw material of flexible ceramics, which becomes a new research interest 2,10–12 …”
Section: Introductionmentioning
confidence: 99%
“…9 Very recently, AT ceramics appear in several reports as the raw material of flexible ceramics, which becomes a new research interest. 2,[10][11][12] However, the significantly large thermal expansion anisotropy of AT ceramics, which, though results in low thermal expansion, induces the grain boundary microcracks and lowers the mechanical strength, limiting its actual applications. 1 Luckily, several attempts have been employed to regulate the microstructure to improve its mechanical properties, including the addition of additives 13,14 and the fabrication of composites.…”
Section: Introductionmentioning
confidence: 99%